PEMBERIAN MP-ASI DINI SEBAGAI SALAH SATU FAKTOR KEGAGALAN ASI EKSKLUSIF PADA IBU PRIIMIPARA (Studi Kasus di Wilayah Kerja Puskesmas Pudakpayung) - Siska Dwi Nugraheni; Priyadi Nugraha Prabamukti; Emmy Riyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Primipara's mother is the first woman to have a live baby so she has no breastfeeding experience yet. Pudakpayung health center with coverage of exclusive plenary milk exclusively that is 14.33%, indicates there are still many mothers who fail in giving exclusive breastfeeding. One of the behaviors that causes exclusive breastfeeding failure is complementary breastfeeding feeding that is too early. This study aims to describe the factors that support complementary feeding of early breastfeeding in primiparous mothers. This study uses a qualitative method. The research subjects were 6 primiparous mothers who failed to provide exclusive breastfeeding because they provided complementary feeding for early breastfeeding. Data collection is done through in-depth interviews. Data were analyzed through data collection, reduction, presentation and conclusion drawing. The results showed that complementary feeding of early breastfeeding was thought to be due to poor mother's knowledge of exclusive breastfeeding, a mother's negative attitude to breastfeeding which should be given 6 months without other foods, and a belief in myth. In addition, the unavailability of tools to store breast milk and negative support from family and friends in the form of advice about complementary feeding of early breastfeeding also supports the failure of primipara mothers in exclusive breastfeeding.